2007
DOI: 10.1308/003588407x155806
|View full text |Cite
|
Sign up to set email alerts
|

Publication Outcome for Research Presented at the Vascular Society of Great Britain and Ireland Annual Meetings

Abstract: BACKGROUND The Vascular Society of Great Britain and Ireland (VSGBI) annual meeting is a major international vascular surgery conference. Studies suggest that the percentage of presentations that result in full-text publications are a measure of the quality of the meeting. We investigated the publication outcome of abstracts presented to the VSGBI in 2001 and 2002.MATERIALS AND METHODS We retrospectively identified abstracts from the conference programmes and conducted a detailed electronic Medline and PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Furthermore, PRPs play an important role in promotion of authors working in academia, and a lesser role in the promotion of those working in private practice. Thus, it is not surprising that, similar to our results, many studies have shown significantly higher publication rates by authors working in universities . However, it is also possible that author affiliation had an effect on other variables, as we did not analyze interaction between variables.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, PRPs play an important role in promotion of authors working in academia, and a lesser role in the promotion of those working in private practice. Thus, it is not surprising that, similar to our results, many studies have shown significantly higher publication rates by authors working in universities . However, it is also possible that author affiliation had an effect on other variables, as we did not analyze interaction between variables.…”
Section: Discussionsupporting
confidence: 87%
“…Since publication rates may be influenced by geographical region of origin of the article, it may not be appropriate to compare publication rates across the globe 14-17. Recent studies show that the publication rates continue to largely vary between 25 and 68%; 17-20 however, some specialty conferences report rates that are higher than 80% 21,22. These authors conclude that high publication rates reflect well on the abstract selection process and the scientific quality of the meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was a relatively small data set representing only 2 consecutive years and 106 abstracts, the reported publication rate was 59.4% in journals with a mean impact factor of 3.5. 10 On the other hand, the reported publication rate following the Canadian Cardiovascular Congresses from 2006 to 2010 and representing 3565 abstracts was only 24.1% in journals with a mean impact factor of 5.2.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A wealth of studies documenting the rates of publication following abstract submission exists, and such studies have often been used as a marker of conference quality both within a particular specialty and across specialties. 3,6,[8][9][10][11][12] The most recent systematic review 6 reports a weighted mean publication rate following a conference presentation of 44.5%; however, the publication rates for individual conferences can vary substantially (8%-81%). With respect to vascular surgery, the Vascular Society of Great Britain and Ireland Annual Meeting of 2001 and 2002 reported mean publication rates of 59.4%, whereas the Canadian Cardiovascular Congress has reported mean publication rates of 24.1%.…”
mentioning
confidence: 99%
See 1 more Smart Citation